A magneto-inductive wave wireless power transfer device. Issue 1 (24th April 2015) - Stevens, Christopher J.
Abstract : Magneto-inductive waves are a form of propagation which only exists in certain types of magnetic metamaterials formed from inductively coupled resonant circuits. We present an investigation of their potential as contactless power transfer devices capable of carrying power along a surface between suitably prepared terminals while simultaneously offering a broadband data channel. Input impedances and their matching conditions are explored with a view to offering a simple power system design. A device with 75% peak and 40% minimum efficiency is demonstrated and designs with potential for better than 70% mean and 90% peak are reported. The product of planar magnetic coupling and metamaterial cell Q factor is determined to be a key optimization parameter for high efficiency.